Eco-friendly Architecture in Developing African Countries: Design and Self-construction of a Playground in Kenya - De Gregorio, Stefania (International Journal of Architectural Engineering Technology, 2023)
Developing countries can seize the opportunity to direct their development by freeing themselves from the mistakes of already developed countries and rooting it towards environmental, economic, and social sustainability. The research has identified a method described in phases that becomes the guarantor of an eco-friendly architecture, which starts from the resources of the territory, enhances them, and returns cyclical processes to the territory that becomes the driving force of development. An initial phase of acquisition of knowledge about the territory is followed by an analysis of its criticalities and potential. Based on these results, the definition of the harvest map (tangible and intangible resources) is conducted, which also includes related construction solutions and the analysis of compatibility with the current production system, to improve it. This method was applied to a case study in Kenya, through the construction of a playground in the external area of a school located in an area adjacent to Makongeni Village, Malindi, Kenya. The playground was built with local wood and waste tires, involving the teachers and students both in the design and construction phases. Eco-friendly architecture can become a driving force for sustainable development. The development of a production system based on local resources makes it possible to produce jobs, with an increase in the well-being of the population, specializing local companies and workers to the detriment of foreign companies and imported materials.